Transcriptomics on Social Interactions in Termites: Effects of Soldier Presence - Matsunami, Masatoshi; Watanabe, Dai; Fujiwara, Kokuto; Hayashi, Yoshinobu; Shigenobu, Shuji; Miura, Toru; Maekawa, Kiyoto (Frontiers in Ecology and Evolution, 2022)
The organization of social insect colonies requires sophisticated mechanisms to regulate caste composition according to colony demands. In termites, the soldier caste is responsible for the inhibition of soldier differentiation, but the mechanism underlying the regulation of soldier differentiation is still unclear. In this study, we performed transcriptome analyses to identify genes expressed in workers that fluctuated in the presence of soldiers in the subterranean termite Reticulitermes speratus. First, soldier differentiation was artificially induced via juvenile hormone (JH) application, and the inhibitory effects of soldier differentiation on soldier presence were evaluated. Second, transcriptomes were prepared from workers with or without soldiers under JH treatment, and expression analyses were performed to identify differentially expressed genes (DEGs) for each treatment. The expression levels of several DEGs were verified by quantitative real-time PCR. The results indicated that only a small number of DEGs were upregulated by the presence of soldiers. A homology search of DEGs and gene ontology (GO) analysis of the DEGs showed that some genes were responsible for the regulation of hormone levels, social interaction, and response to xenobiotic substances, suggesting that they could be involved in developmental arrest and pheromonal regulation in workers. Moreover, GO analysis indicated that the expression of many genes, including those involved in hormone metabolic processes, fluctuated with JH application. Suppression of soldier differentiation in the presence of soldiers could be accomplished by the expression of a large number of genes required for soldier differentiation.